2021
DOI: 10.1002/lary.29918
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Academic Laryngology: An Evaluation of Academic Advancement and Research Productivity

Abstract: Background: Diversity within the medical profession with respect to sex and racial minorities has been shown to have a positive effect on health and healthcare. Characterization of a field is key to evaluating trends and the advancement of diversity in an otolaryngology subspecialty.Study Design: Observational study. Methods: A comprehensive list of all the academic laryngologists was compiled from the Accreditation Council for Graduate Medical Education accredited otolaryngology residency programs in 2020. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…• Attrition from medical school 61,64 • Lower acceptance rates into residency 7,10,57 • Attrition from residency programs and fellowships 13,14 • Lower proportions of URiM faculty receiving tenure track positions [47][48][49] • Lower rates of promotion [15][16][17][18]50 • Fewer URiM chairs and deans 119 Across medical specialties, URiM trainees and faculty are less likely to get accepted into training programs, to be hired into tenure positions, to be promoted, and to hold chair or dean positions. [7][8][9][10][11][12][120][121][122][123][124][125][126][127][128][129][130][131] Chilly climate An environment in which discrimination, both subtle and overt, creates a hostile work environment and unequal treatment of different groups…”
Section: Pathways and Potholesmentioning
confidence: 99%
See 1 more Smart Citation
“…• Attrition from medical school 61,64 • Lower acceptance rates into residency 7,10,57 • Attrition from residency programs and fellowships 13,14 • Lower proportions of URiM faculty receiving tenure track positions [47][48][49] • Lower rates of promotion [15][16][17][18]50 • Fewer URiM chairs and deans 119 Across medical specialties, URiM trainees and faculty are less likely to get accepted into training programs, to be hired into tenure positions, to be promoted, and to hold chair or dean positions. [7][8][9][10][11][12][120][121][122][123][124][125][126][127][128][129][130][131] Chilly climate An environment in which discrimination, both subtle and overt, creates a hostile work environment and unequal treatment of different groups…”
Section: Pathways and Potholesmentioning
confidence: 99%
“…Conceptual Groupings Identified in the Scoping Review Within the Leaky Pipeline[119][120][121][122][123][124][125][126][127][128][129][130][131] …”
mentioning
confidence: 99%
“…
We commend The Laryngoscope for promoting scholarship around diversity, equity, and inclusion in otolaryngologyhead and neck surgery. [1][2][3][4][5][6] We read with interest the article by Uppal and colleagues on otolaryngology departmental and societal leadership. 7 The authors found that otolaryngology has an underrepresentation of women and specific ethnic-racial group leadership, underscoring the importance of recognizing underrepresented women leaders in medicine.
…”
mentioning
confidence: 99%